2019
DOI: 10.1371/journal.pone.0216735
|View full text |Cite
|
Sign up to set email alerts
|

Comparing genotype and chemotype of Fusarium graminearum from cereals in Ontario, Canada

Abstract: Fusarium graminearum is responsible for production of the mycotoxin deoxynivalenol (DON) on maize and wheat in Ontario, Canada. It has been understood since the early 1980s that in most parts of Canada, the predominant chemotype of F . graminearum is 15ADON, and not the 3ADON chemotype mainly found in Europe and Asia. The discovery of F . graminearum strains that did not produce DON but the structurally relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 72 publications
0
43
2
Order By: Relevance
“…These ascocarps can act as a primary inoculum in newly established wheat fields and can result in the establishment of further 15ADON populations. When comparing the genotypes and chemotypes of F. graminearum from maize and wheat samples from farms in Ontario, Crippin et al (2019) confirmed that 15ADON is the predominant chemotype in eastern Canada and reported that 3ANX (15-deacetylcalonectrin) toxin production occurs concurrently with 15ADON. They also suggested that the 3ANX producers in North America probably originated from a 15ADON background.…”
Section: Trichothecene Mycotoxin Chemotypes and The Population Genetic Structures Of Fusarium Species Causing Fhb In Wheat And Barleymentioning
confidence: 74%
“…These ascocarps can act as a primary inoculum in newly established wheat fields and can result in the establishment of further 15ADON populations. When comparing the genotypes and chemotypes of F. graminearum from maize and wheat samples from farms in Ontario, Crippin et al (2019) confirmed that 15ADON is the predominant chemotype in eastern Canada and reported that 3ANX (15-deacetylcalonectrin) toxin production occurs concurrently with 15ADON. They also suggested that the 3ANX producers in North America probably originated from a 15ADON background.…”
Section: Trichothecene Mycotoxin Chemotypes and The Population Genetic Structures Of Fusarium Species Causing Fhb In Wheat And Barleymentioning
confidence: 74%
“…Their behavior was identical in one aspect: all inhibited the peak production of 15-ADON produced by F. graminearum (see Figure A2A). 15-ADON is a precursor to the formation of DON [44]. This inhibition could therefore be a sign of an action on the biosynthesis pathway, in particular the Tri8 gene involved in the transformation of 15-ADON into DON.…”
Section: Discussionmentioning
confidence: 99%
“…For an historical account of the development of primers and PCR conditions for Fusarium genotyping see review by Pasquali and Migheli [96]. Specific TRI genes enabled differentiation between different trichothecenes: TRI3 and TRI12, for the differentiation of genotypes into 3-ADON, 15-ADON, or NIV [73,74,78,81,83,91,97] TRI7 and TRI13, for the differentiation of genotypes into DON and NIV [74,81,83,91]; and TRI1 along with its regulatory genes TRI6 and TRI10 [39] and TRI3 and TRI12 [83,98], for the differentiation of 3ANX (NX-2) and NX (NX-3) from 3-ADON, 15-ADON, and DON [82].…”
Section: Genotyping Platformsmentioning
confidence: 99%
“…Some studies reported that genotyping was highly correlated to chemotyping and that trichothecene genotyping enabled rapid prediction of production of different toxins [74,83,90,95,108,134,135]. Other studies report incongruence between chemotype and genotype data and warn against using genotyping to solely identify the risk of mycotoxin production [19,37,82,87,136,137].…”
Section: Incongruence Between Chemotype and Genotypementioning
confidence: 99%